2014
DOI: 10.3390/sym6020345
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processes in Prochiral Solvating Agents (pro-CSAs) Studied by NMR Spectroscopy

Abstract: Several dynamic processes, including tautomerism and macrocyclic inversion, in 1H-NMR prochiral solvating agents (pro-CSAs) are investigated. Various features of pro-CSA, including modes of interaction for complex formation, stoichiometry, binding strength and temperature effects were compared for three representative pro-CSA molecules. Structural effects of conjugated tetrapyrrole pro-CSA on the mechanism of enantiomeric excess determination are also discussed. Detailed analysis of species (complexes) and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It is notable that ee -dependent NMR splitting in the coordination complex occurs even in dilute solution due to the lack of chiral guest dissociation in the coligand exchange system. Thus, this is in contrast to a previously reported hydrogen-bonded host–guest system. This work provides evidence for pro -CSA activity in coordination complexes, gives new insights into chiral transfer events in metal–ligand complexes, and suggests a substantial new subject of investigation for chiral processes involving dynamic coordination bonding.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…It is notable that ee -dependent NMR splitting in the coordination complex occurs even in dilute solution due to the lack of chiral guest dissociation in the coligand exchange system. Thus, this is in contrast to a previously reported hydrogen-bonded host–guest system. This work provides evidence for pro -CSA activity in coordination complexes, gives new insights into chiral transfer events in metal–ligand complexes, and suggests a substantial new subject of investigation for chiral processes involving dynamic coordination bonding.…”
mentioning
confidence: 61%
“…Enantiomers of a chiral substance have nonsuperimposable structures but exhibit identical nuclear magnetic resonance (NMR) spectra. , Thus, it is not possible to determine the enantiomeric excess ( ee ) of a chiral substance from NMR spectra of simple mixtures of enantiomers. However, we have found that the addition of a symmetrical prochiral host molecule to solutions containing chiral analytes can be used to estimate ee through a mechanism involving rapid exchange of hydrogen-bonded analyte–host complexes. In those systems, NMR resonances of the prochiral host molecules show ee dependent splitting due to an averaging of chemical shift nonequivalency induced by the chiral analyte. For this to occur, host symmetry requirements and guest binding strength are critical parameters in the intermolecular information transfer process and eventually allow chiral information to be retrieved from the NMR spectrum of the prochiral host.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds of the type OxPBz 2 are excellent examples of what we have come to refer to as prochiral solvating agents (pro-CSAs, see Figure 6a) [43,76]. If a single enantiomer guest (Figure 6b) is added to OxPBz 2 in solution, there occurs a symmetrical splitting of the relevant reporter resonances of OxPBz 2 (Figure 6c).…”
Section: Oxoporphyrinogens and Porphyrin Dicationsmentioning
confidence: 99%